2011
DOI: 10.1002/ana.22468
|View full text |Cite
|
Sign up to set email alerts
|

Circadian activity rhythms and risk of incident dementia and mild cognitive impairment in older women

Abstract: Objective Previous cross-sectional studies have observed alterations in activity rhythms in dementia patients but the direction of causation is unclear. We determined whether circadian activity rhythms measured in community-dwelling older women are prospectively associated with incident dementia or mild cognitive impairment (MCI). Method Activity rhythm data were collected from 1,282 healthy community-dwelling women from the Study of Osteoporotic Fractures cohort (mean age 83 years) with wrist actigraphy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
330
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 425 publications
(370 citation statements)
references
References 94 publications
(170 reference statements)
18
330
2
2
Order By: Relevance
“…Our analysis of the circadian rhythm in gross behaviour shows that there are not significant differences between the declined and the intact groups in terms of the rhythm amplitude, MESOR or percentage of variance in the activity rhythm explained by the 24-h co-sinor regression model, but that those in the declined group showed a peak in their activity rhythm that was significantly later than that for the intact group. This finding appears to be in agreement with the recent report from Tranah et al (2011), who in a large prospective study found that delayed behavioural rhythm was a significant predictor of developing MCI or dementia. However, these authors also report that dampened circadian amplitude and robustness of the rhythm were also predictors of MCI/dementia, findings that are not recapitulated in our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our analysis of the circadian rhythm in gross behaviour shows that there are not significant differences between the declined and the intact groups in terms of the rhythm amplitude, MESOR or percentage of variance in the activity rhythm explained by the 24-h co-sinor regression model, but that those in the declined group showed a peak in their activity rhythm that was significantly later than that for the intact group. This finding appears to be in agreement with the recent report from Tranah et al (2011), who in a large prospective study found that delayed behavioural rhythm was a significant predictor of developing MCI or dementia. However, these authors also report that dampened circadian amplitude and robustness of the rhythm were also predictors of MCI/dementia, findings that are not recapitulated in our study.…”
Section: Discussionsupporting
confidence: 93%
“…These authors report that dampened activity rhythms was a significant predictor for the development of both dementia and MCI, as was a later peak of activity rhythm, suggesting that circadian amplitude and phase may be significant factors in the development of these conditions. Interestingly, these effects were also found to be independent of sleep effects (Tranah et al (2011)). The role of actigraphically determined daytime activity in MCI and dementia was further examined by Kuhlmei et al (2011) who report that reduced activity in both dementia and MCI was present when apathy was also present.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Further evidence for the importance of circadian rhythms in AD is provided by the finding that higher daytime activity levels and lower nocturnal activity (i.e., consolidated, nonfragmented sleep/wake cycle organization), is strongly associated with increased wellbeing and functional status (20). Results from a large prospective study indicate that changes in circadian activity patterns (decreased rhythm amplitude, phase-delays) are significant predictors of subsequent AD or mild cognitive impairment, suggesting that compromised rhythms might be a preclinical phenomenon (21). Another point of interest is that anti-psychotic medication used in the clinical management of AD might impact on circadian rhythms (22), because these medications might impact on the molecular components of the circadian system (23).…”
Section: Functional Studies Of Circadian Disruption In Admentioning
confidence: 99%